دور قطاع البناء والتشييد في بناء الاقتصاد الوطني - العمار, رضوان; صقر, محمد; الأسد, هلال أنور (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث مدى مساهمة قطاع البناء والتشييد في بناء الاقتصاد الوطني وذلك من خلال مساهمته في الناتج المحلي بالأسعار الجارية والثابتة, حيث يهدف هذا القطاع, الذي يشكل جزءاً هاماً من الاقتصاد الوطني في الجمهورية العربية السورية إلى تحقيق زيادة في الناتج المحلي وتحقيق النمو الاقتصادي وذلك من خلال بناء القاعدة التحتية في الاقتصاد. فقد ركز البحث على بيان النسبة المئوية للتركيب الهيكلي لإنتاج قطاع البناء والتشييد وحصة الناتج المحلي الإجمالي لقطاع البناء والتشييد من الناتج القومي بسعر المنتج, كما تم بيان الأسباب التي أدت إلى تراجع هذا القطاع في القطر العربي السوري في الفترة ما بين (1990-2003). This paper studies the extent of the contribution of the building sector to building the national economy through its contribution to the domestic product at fixed and current prices. Being an important part of the national economy in the Syrian Arab Republic, this sector aims to achieve an increase in the domestic product and achieve economic growth by building the economic infrastructure.This study has concentrated on showing the percentage of the structure for the production of the construction and building sector, and the share of the gross domestic product off the national product at product prices. We have also shown the reasons that have led to the deterioration of this sector in the Syrian Arab Republic (1990-2003).